Biology and habits of Ensine hyallipennis (Diptera: Tephritidae) y tiomoeosome oconequensis (Lepidoptera: Pyralidae), weeds phytophagous insects in the Sabana de Bogotá - NÁJAR-R., ADRIANA J.; ESPITIA-M., EDUARDO; ARRIETA, J. MANUEL (Revista Colombiana de Entomología, 2001)
The fly Ensina hyallipennis (Diptera: Tephritidae) and the moth Homoeosoma oconequensis (Lepidoptera: Pyralidae) are two phytophagous insects registered in Colombia for the first time. Their larvae are seed feeders of the composite weeds "cerraja" Sonchus oleraceus and "escobilla" Senecio inaequidens. These weeds, highly aggressive in the cold areas in Colombia, are very difficult to eradicate in conventional ways. This research was conducted in order to evaluate the insect's potential of biocontrol through the study of some aspects of their life history, hábitats. infestation levels, field damage, and naturalenerníes. The results show that the fly E. hyallipennis had high infestation levels and field damage of 94.2% affected plants and 72.5% affected head flowers/plant; its life cycle was completed in laboratory conditions in 20 average days. into the affected head flowers, which arrives at the ripening with few or none seed. Furthermore, natural enemies were not found in understudied conditions. On the other hand, the moth H. oconequensis has an acceptable control potential on S. inaequidens because it has very low infestation levels and field damage of 9.8% affected plants and 10.6% affected head flowers; its life cycle was completed in laboratory conditions in 62 average days. The consumption of the immature seeds and the prevention head flower ripening was the damage. As a natural enemy, a fly (Díptera: Tachínídae) parasitoid was found, which can reduce its field control potential.